Az MVM OVIT Zrt. Hálózati Igazgatóság működésében bekövetkezett változások a projektorientált szervezet megalakulását követően - Tóth Imre (2018)
The main goal of companies is to increase their profits every year. This can be achieved by increasing the number of projects acquired. However, it is not enough just to accumulate the work, someone has to do it as well. In order for the projects to be transformed into profit after the implementation, a stable, cooperating, success-oriented team is needed. A well-formed team, where sub- and superordinations and tasks assigned to certain jobs are properly defined, is a great advantage during execution. Furthermore the project management is not about to start a project and leave on its own, it must be constantly cont-rolled and analyzed. One of the most important thing is the exploration and analysis of "faults" discovered during the implementation process and value them after the project closure, do that in future they will not block the operation of the project and thus the suc-cess of the company. There are many opportunities for companies to select back-up support systems that make it easier for project managers to do so, so keeping track of economic indicators du-ring the execution of the projects will make it easier for the particular leader to work. However, it is a neat task to develop a system that satisfies the needs of everyone. In my thesis, I present the changes that can be predicted during the operation of MVM OVIT Zrt. Thanks to the predictability or the rapid reaction of the company, these changes have taken place just in time and almost in an uninterrupted manner. However, most changes do not only have positive, but negative effects. The explo-ration and remedy of these are essential for later functioning of the organization. I have al-so tried to describe these suggestions as accurately as possible. In addition to the development of an appropriate organization and continuous development, another important thing for companies is to examine their economy, which plays a decisive role in the company's operation. The most comprehensive picture is the analysis based on the reports, so I try to use this analytical tool to illustrate the effects of change. For the operation of companies, in my opinion, it is essential to outline a medium-term strategy that sets out goals and adjusts their operation to achieve these goals. The mission of MVM OVIT is to become the market leader in the energy market of Hungary, while its efficiency, steady progress continue to function.